Effect of ionic liquid electrolytes on the electrochemical stability and optical tunability of polyaniline-based infrared variable emittance devices. (20th October 2020) - Li, Xiaobai; Zhang, Leipeng; Xu, Gaoping; Wang, Bo; Yu, Shuang; Ren, Zichen; Ren, Feifei; Dou, Shuliang; Li, Yao; Zhao, Jiupeng
Highlights: The electrochemical behaviors of PANI in eight IL electrolytes were studied. IL anions had a significant influence on the cycling stability of PANI films. Different ILs used had a great effect on the IR tunability of PANI films. The IR-VED using a preferred ionogel electrolyte had good overall performance. Abstract: In this study, ionic liquids (ILs) are used instead of conventional volatile aqueous or organic electrolytes to fabricate durable polyaniline (PANI)-based infrared variable emittance devices (IR-VEDs). It is of significance to find that different IL electrolyte systems have a great effect on the electrochemical stability and IR tunability of the PANI films. The present PANI films exhibit much better electrochemical stability when cycling in ILs having tetrafluoroborate and bis(trifluoromethylsulfonyl)imide anions than cycling in ILs with dicyanamide and tricyanomethanide anions. Furthermore, compared with pure IL electrolytes, the addition of high-mobility cations (Li + ) into ILs can significantly enhance the IR tunability of PANI films. The IR-VED based on a preferable ionogel electrolyte membrane exhibits a high emittance variation (Δԑ) of 0.42 in 2.5–25 µm region, and fast switching times of 14.6 s/17.0 s. More importantly, the device still maintains a high Δԑ value of 0.35 after 500 electrochemical cycles, demonstrating promising applications in the dynamic IR regulation field. Graphical abstract: Image, graphical abstract